Pengaruh Intellectual Capital, Earnings Management, Tax Avoidance Terhadap Nilai Perusahaan dengan GCG sebagai Pemoderasi - Verawaty Verawaty; Citra Indah Merina; Setri Ayu Lastari (MBIA, 2017)
The purpose of this research was to know the influence of Intellectual Capital, Earnings Management, and Tax Avoidance to the company's value with Good Corporate Governance as the moderating variable in the banking company listed on the Indonesia Stock Exchange in 2015. This study used the quantitative approach. The data were obtained from the annual report of the banking company. After going through the stage of purposive sampling, the sample was 38 companies. Technique of data analysis used the classic assumption test and multiple linear analysis. The study results indicated that Intellectual Capital, Earnings Management and Tax Avoidance does not affect company's value. While the Intellectual Capital that was moderated by Good Corporate Governance had significant influence to company's value and Earnings Management that moderated by Good Corporate Governance did not influence company's value.